Nighttime warming enhances ecosystem carbon‐use efficiency in a temperate steppe. (14th May 2020) - Wang, Jing; Zhang, Qian; Song, Jian; Ru, Jingyi; Zhou, Zhenxing; Xia, Jianyang; Dukes, Jeffrey S.; Wan, Shiqiang
Abstract: Reductions in the diurnal temperature range (DTR), for example, greater increases in daily minimum than maximum temperatures, have occurred for several decades and are projected to continue over this century, which could affect terrestrial carbon (C) cycling. Carbon‐use efficiency of plants (CUEp) and ecosystems (CUEe) represents the capacity of plants to capture C and ecosystems to store C fixed from the atmosphere, respectively. Few studies have examined how grassland CUE responds to asymmetric warming. As part of a long‐term (2006–2016) field experiment that simulated daytime and nighttime warming in a semi‐arid temperate steppe on the Mongolian Plateau, this study was conducted to examine the effects of daytime and nighttime warming on CUEp and CUEe. Nighttime warming, unlike daytime warming, increased CUEe by 54.2%, whereas neither nighttime nor daytime warming affected CUEp. Ecosystem‐level CUE linearly increased with soil moisture but declined with soil temperature variation (CVST ). The suppressed ER, which might have been driven by the reduced CVST, primarily contributed to the higher CUEe under nighttime warming. These observations indicate that a reduced DTR, associated with a warmer night under asymmetric diurnal climate warming, could increase the capacity of the temperate steppe transferring C into ecosystems by elevating CUEe, resulting more C sequestration. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article